Cylindrical battery cell, battery device, electric device
Patent Information
- Application Number
- CN202610842472.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2026-02-09
- Filing Date
- 2026-06-11
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-06-11
Smart Images

Figure CN122393507B_ABST
Abstract
Description
[0001] Cross-references to related applications
[0002] This application claims priority to PCT patent application PCT / CN2026 / 077973, filed on February 9, 2026, entitled “Cylindrical Battery Cell, Battery Device, Electrical Device”, the entire contents of which are incorporated herein by reference. Technical Field
[0003] This disclosure pertains to a cylindrical battery cell, a battery device, and an electrical device. Background Technology
[0004] Battery cells, especially cylindrical battery cells, are widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric cars, electric airplanes, electric ships, electric toy cars, electric toy ships, electric toy airplanes, and power tools. With the development of cylindrical battery cells, the performance requirements for them are also gradually increasing. How to achieve high energy density, long cycle life, and good thermal runaway stability in cylindrical battery cells is a pressing technical problem that needs to be solved. Summary of the Invention
[0005] This disclosure provides a cylindrical battery cell, a battery device, and an electrical device. The cylindrical battery cell has high energy density, long cycle life, and good thermal runaway stability.
[0006] In a first aspect, embodiments of this disclosure provide a cylindrical battery cell, comprising: a casing made of metal; an electrode assembly and an electrolyte, housed within the casing; the casing includes a housing and an end cap, the housing including a side wall and an end wall connected to the side wall, the housing having an opening, the end cap connected to the side wall and covering the opening, and the end cap and the end wall being opposite each other along the axial direction of the cylindrical battery cell; the surface of the end cap having an explosion-proof valve, the explosion-proof valve occupying 10% to 40% of the surface area of the end cap; the electrode assembly including a negative electrode and a positive electrode, the positive electrode including a positive current collector and a positive electrode film, at least one side of the positive current collector having a positive electrode film, the positive electrode film including a positive active material, the positive active material including nickel-lithium. The transition metal oxide, including nickel-lithium transition metal oxide, includes a modifying element M, which includes one or more of B, Y, Nb, Sn, Zr, Ti, W, Ca, Sr, S, F, Na, K, V, Ta, and Mg. The mass percentage of the modifying element M in the positive electrode film is 0.01% to 0.4%. Based on the total mass of the transition metals in the nickel-lithium transition metal oxide, the mass percentage of Ni element is greater than or equal to 50%. The electrolyte includes functional additives, which include one or more of sulfur-containing additives, boron-containing additives, fluorine-containing additives, and carbonate additives. The mass percentage of the functional additives in the electrolyte is 0.05% to 7%.
[0007] The explosion-proof valve disclosed herein has an area ratio of greater than or equal to 10%, which allows the gas and energy inside the cylindrical battery cell to be smoothly discharged during pressure relief, thus mitigating thermal runaway and improving thermal runaway stability. The explosion-proof valve disclosed herein has an area ratio of less than or equal to 40%, which allows the explosion-proof valve to open at a moderate pressure threshold, reducing the risk of premature valve opening and also reducing the intensity of thermal runaway.
[0008] The modified element M disclosed herein has a mass percentage of 0.01% to 0.4% in the positive electrode film layer, which can enable the cylindrical battery cell to have high energy density, long cycle life and thermal runaway stability.
[0009] While lower levels of modifying elements can result in higher energy density in cylindrical battery cells, the modification effect is less pronounced, leading to more gas production. If the area ratio of the explosion-proof valve is too high, the excessive pressure it experiences can cause premature valve opening, resulting in valve failure and impacting the cycle performance of the cylindrical battery cell. Furthermore, it hinders the control of subsequent thermal runaway stability. Conversely, if the area ratio of the explosion-proof valve is too low, it impedes the smooth discharge of gas and energy from within the cylindrical battery cell during thermal runaway valve opening, reducing thermal runaway stability. Therefore, the modified element content disclosed in this invention works synergistically with the area ratio of the explosion-proof valve to achieve high energy density, long cycle life, and thermal runaway stability in the cylindrical battery cell.
[0010] In some embodiments, the area of the explosion-proof valve on the end cap surface accounts for 10% to 30%.
[0011] Explosion-proof valves with the above-mentioned area ratio can enable cylindrical battery cells to have higher energy density, better cycle life and better thermal runaway stability.
[0012] In some embodiments, the modified element M accounts for 0.1% to 0.4% of the mass of the positive electrode film.
[0013] Modifying element M with the above-mentioned mass proportions can enable cylindrical battery cells to have higher energy density, better cycle life, and better thermal runaway stability.
[0014] In some embodiments, the mass percentage of Ni element is 80% to 97% based on the total mass of the transition metal in the nickel-lithium transition metal oxide.
[0015] Ni with the above-mentioned mass percentage can enable cylindrical battery cells to have higher energy density, better cycle life and better thermal runaway stability.
[0016] In some embodiments, the explosion-proof valve accounts for 20% to 30% of the area on the end cap surface, the modified element M accounts for 0.25% to 0.4% of the mass in the positive electrode film layer, and the Ni element accounts for 85% to 92% of the mass based on the total mass of the transition metal in the nickel-lithium transition metal oxide.
[0017] The aforementioned explosion-proof valve, modified elements M and Ni can work synergistically to give cylindrical battery cells higher energy density, longer cycle life and better thermal runaway stability.
[0018] In some embodiments, when the modifying element M is one or more of B, Y, Nb, Sn, Zr, Ti, W, Sr, V and Ta, the mass percentage of the modifying element M in the positive electrode film layer is 0.03% to 0.2%.
[0019] With the aforementioned modifying element M, nickel-lithium transition metal oxides can have high specific capacity, improve surface stability, reduce side reactions between nickel-lithium transition metal oxides and electrolytes, and reduce gas production. This enables cylindrical battery cells to have both high energy density and long cycle life.
[0020] In some embodiments, when the modifying element M is one or more of S and F, the mass percentage of the modifying element M in the positive electrode film layer is 0.02% to 0.1%.
[0021] With the aforementioned modifying element M, nickel-lithium transition metal oxides can have high specific capacity, improve surface stability, reduce side reactions between nickel-lithium transition metal oxides and electrolytes, and reduce gas production. This enables cylindrical battery cells to have both high energy density and long cycle life.
[0022] In some embodiments, when the modifying element M is one or more of Mg, Na, K and Ca, the mass percentage of the modifying element M in the positive electrode film layer is 0.05% to 0.2%.
[0023] With the aforementioned modifying element M, nickel-lithium transition metal oxides can have high specific capacity, improve surface stability, reduce side reactions between nickel-lithium transition metal oxides and electrolytes, and reduce gas production. This enables cylindrical battery cells to have both high energy density and long cycle life.
[0024] In some embodiments, the nickel-lithium transition metal oxide particles include an inner region and an outer region. The outer region refers to the area from the outer surface of the particle to a depth of 500 nm in the direction toward the geometric center of the particle. The outer region surrounds the outer periphery of the inner region. Both the inner and outer regions are provided with the modifying element M.
[0025] In some embodiments, the positive electrode active material includes a nickel-lithium transition metal oxide matrix and a coating layer disposed on at least a portion of the surface of the nickel-lithium transition metal oxide matrix, the coating layer including one or more of cobalt oxide and aluminum oxide, and the Dv50 of the positive electrode active material is 1 μm to 5 μm.
[0026] A Dv50 greater than or equal to 1 μm for the positive electrode active material results in a lower specific surface area, reducing the number of active sites that may react with the electrolyte and decreasing gas production. Conversely, a Dv50 less than or equal to 5 μm allows for a higher compaction density in the positive electrode film, increasing the energy density of the cylindrical battery cell. This, in turn, improves the cycle life and energy density of the cylindrical battery cell.
[0027] In some embodiments, the positive electrode active material includes a nickel-lithium transition metal oxide matrix and a coating layer disposed on at least a portion of the surface of the nickel-lithium transition metal oxide matrix, the coating layer including one or more of cobalt oxide and aluminum oxide, and the Dv50 of the positive electrode active material is 1.5 μm to 4 μm.
[0028] Positive active materials with the aforementioned Dv50 can better improve the long cycle life and high energy density of cylindrical battery cells.
[0029] The elemental composition of the coating layer on at least part of the surface of a nickel-lithium transition metal oxide substrate can be qualitatively analyzed by combining characterization methods such as EDS energy dispersive spectroscopy.
[0030] The volume distribution particle size Dv50 of the positive electrode active material is a commonly used definition in the art, representing the particle size corresponding to a cumulative volume distribution percentage of 50% of the material. It can be determined using instruments and methods known in the art. For example, it can be determined using a laser particle size analyzer, referring to GB / T 19077-2016. The testing instrument can be the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0031] In some embodiments, the positive electrode active material includes single-crystal particles and polycrystalline particles, wherein the area ratio of polycrystalline particles in the positive electrode film layer is 50% to 90%.
[0032] This can reduce the amount of fresh interface exposed by cracking of the positive electrode active material, reduce the contact area between the positive electrode active material and the electrolyte, and reduce side reactions. On the other hand, it can give full play to the advantages of high specific capacity, good cycle performance and good kinetic performance of nickel-containing lithium transition metal oxide particles with high nickel content and polycrystalline morphology. Thus, cylindrical battery cells can have both high energy density and good cycle performance.
[0033] In some embodiments, the molar percentage of Ni in the transition metal elements of the nickel-lithium transition metal oxide is above 85%.
[0034] Ni has a high molar percentage in transition metals in nickel-lithium transition metal oxides, which can give cylindrical battery cells higher energy density.
[0035] In some embodiments, the reversible specific capacity of the nickel-lithium transition metal oxide is from 200 mAh / g to 225 mAh / g.
[0036] In some embodiments, the nickel-lithium transition metal oxide further includes the general formula Li a Ni b A c O e The nickel-lithium transition metal oxide matrix, wherein 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 1≤e≤2, and A includes one or more of Mn, Al and Co.
[0037] In some embodiments, the negative electrode sheet includes a negative current collector and a negative electrode film layer. The negative current collector has a negative electrode film layer on at least one side. The negative electrode film layer includes a negative electrode active material, which includes one or more of silicon-based materials and carbon-based materials.
[0038] In some embodiments, the carbon-based material includes one or more of artificial graphite, natural graphite, hard carbon, and soft carbon.
[0039] In some embodiments, silicon-based materials include one or more of silicon-carbon materials, elemental silicon, silicon oxides, silicon-nitrogen composites, and silicon alloys.
[0040] In some embodiments, the mass percentage of Si element in the negative electrode film layer is 3% to 20%.
[0041] The aforementioned negative electrode film can both increase the energy density of the cylindrical battery cell and reduce the volume expansion of the negative electrode sheet. This reduces the risk of premature opening of the explosion-proof valve caused by the volume expansion of the negative electrode, thus enabling the cylindrical battery cell to have good thermal runaway stability.
[0042] In some embodiments, the silicon-based material includes a silicon-carbon material, which includes a porous carbon substrate and silicon located in the pores of the porous carbon substrate.
[0043] The porosity of the porous carbon substrate can reduce the volume expansion of silicon, thereby reducing the risk of premature opening of the explosion-proof valve caused by the volume expansion of the negative electrode, and enabling the cylindrical battery cell to have good thermal runaway stability.
[0044] In some embodiments, the negative electrode film layer includes a first film layer away from the negative electrode current collector and a second film layer close to the negative electrode current collector. The first film layer includes silicon-based materials and carbon-based materials, and the second film layer includes carbon-based materials. The silicon-based materials also include alkali metal elements and / or alkaline earth metal elements, and the mass percentage of silicon elements in the silicon-based materials is 2% to 70%.
[0045] The aforementioned negative electrode film can balance high energy density and low volume expansion. This can improve the energy density and cycle life of cylindrical battery cells.
[0046] In some embodiments, the negative electrode film layer includes a first film layer away from the negative electrode current collector and a second film layer close to the negative electrode current collector. The first film layer includes silicon-based materials and carbon-based materials, and the second film layer includes carbon-based materials. The silicon-based materials also include alkali metal elements and / or alkaline earth metal elements, and the mass percentage of silicon elements in the silicon-based materials is 2% to 20%.
[0047] The aforementioned negative electrode film layer can better balance high energy density and low volume expansion. This can improve the energy density and cycle life of cylindrical battery cells.
[0048] Cut the negative electrode sheet along a direction perpendicular to the surface of the negative electrode film, and use a scanning electron microscope to obtain a cross-sectional SEM image of the negative electrode film in the thickness direction, or use a scanning electron microscope combined with an energy dispersive spectroscopy (EDS) instrument to obtain a cross-sectional SEM-EDS image of the negative electrode film in the thickness direction. The first negative electrode film and the second negative electrode film can be easily distinguished from the images.
[0049] The mass percentage of silicon in silicon-based materials can be measured using an inductively coupled plasma optical emission spectrometer (ICP). The testing standard can be found in JY / T 015 1996.
[0050] In some embodiments, the electrolyte includes functional additives, which include one or more of sulfur-containing additives, boron-containing additives, fluorine-containing additives, and carbonate additives, and the functional additives account for 0.05% to 7% of the mass of the electrolyte.
[0051] The electrolyte described above enables cylindrical battery cells to have a long cycle life.
[0052] In some embodiments, the sulfur-containing additive includes one or more of 1,3-propenesulfonate lactone, vinyl sulfate, and vinyl sulfite.
[0053] In some embodiments, the boron-containing additive includes one or more of lithium difluorophosphate and lithium bis(oxalato)borate.
[0054] In some embodiments, the fluorinated additives include one or more of fluoroethylene carbonate, lithium difluorooxalate borate, and lithium difluorophosphate.
[0055] In some embodiments, carbonate additives include one or more of dimethyl carbonate, ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate.
[0056] In some embodiments, the electrolyte further includes an electrolyte salt, which includes one or more of lithium hexafluorophosphate, lithium difluorophosphate, and lithium bis(oxalato)borate.
[0057] In some embodiments, the molar concentration of the electrolyte salt is from 0.7 mol / L to 1.5 mol / L.
[0058] When the molar concentration of the electrolyte salt is within the above range, it is beneficial to further improve the stability of the electrolyte salt and to improve the conductivity and ion migration rate of the electrolyte, thereby improving the cycle performance of the cylindrical battery cell.
[0059] In some embodiments, the electrode assembly further includes a separator membrane located between the positive electrode and the negative electrode. The separator membrane includes a base film and a coating located on at least one side of the base film. The coating includes a first coating away from the base film and a second coating close to the base film. The first coating includes ceramic particles, and the second coating includes polymer particles.
[0060] The first coating includes ceramic particles, which can form a high-temperature resistant layer, allowing the separator to still block the positive and negative electrodes during thermal runaway, thus improving the stability of the cylindrical battery cell. The second film layer includes polymer particles, which can improve the adhesion between the coating and the base film, reduce the risk of coating peeling off, and improve the stability of the cylindrical battery cell.
[0061] In some embodiments, the base material of the sidewall is steel, and the thickness of the sidewall is 0.2 mm to 0.6 mm.
[0062] In some embodiments, the dimension of the housing along the axial direction of the cylindrical battery cell is 1.3 to 2.6 times the outer diameter of the housing.
[0063] In some embodiments, the housing has an axial dimension of 50 mm to 150 mm along the cylindrical battery cell.
[0064] In some embodiments, the outer diameter of the housing is 30 mm to 80 mm.
[0065] In some embodiments, the outer diameter of the housing is 40 mm to 60 mm.
[0066] Secondly, embodiments of this disclosure provide a battery device comprising a plurality of cylindrical battery cells as described in the first aspect.
[0067] Thirdly, embodiments of this disclosure provide an electrical device, including a cylindrical battery cell of the first aspect or a battery device of the second aspect. Attached Figure Description
[0068] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings used in the embodiments of this disclosure will be briefly introduced below. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0069] Figure 1 This is a schematic diagram of the structure of a vehicle provided for some embodiments of this disclosure.
[0070] Figure 2 This is a schematic diagram of the structure of a battery device provided in some embodiments of this disclosure.
[0071] Figure 3 for Figure 2 The diagram shows the structure of the battery module.
[0072] Figure 4 This is a schematic diagram of the structure of a cylindrical battery cell provided in some embodiments of this disclosure.
[0073] Figure 5 for Figure 4 The diagram shows an exploded view of a cylindrical battery cell.
[0074] The accompanying drawings are not drawn to scale.
[0075] The annotations in the attached figures are explained as follows: 1. Vehicle; 2. Battery unit; 3. Controller; 4. Motor; 5. Housing; 5a. First housing; 5b. Second housing; 6. Battery module; 7. Cylindrical battery cell; 10. Electrode assembly; 20. Housing; 21. Shell; 211. End wall; 212. Side wall; 22. End cap; 1111. Positive electrode tab; 1211. Negative electrode tab; 30. Electrode terminal; 40. First current collector; 50. Second current collector; Z, Axial direction. Detailed Implementation
[0076] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the cylindrical battery cell, battery assembly, and power-consuming device of this disclosure. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this disclosure and are not intended to limit the subject matter of the claims.
[0077] In this disclosure, the reference to "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this disclosure. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment that is mutually exclusive with other embodiments.
[0078] In the description of this disclosure, it should be noted that, unless otherwise expressly specified and limited, the terms "installation," "connection," "linking," and "attachment" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection between two components. Those skilled in the art can understand the specific meaning of the above terms in this disclosure according to the specific circumstances.
[0079] In the description of this disclosure, unless otherwise specified, "above" or "below" the second feature can mean that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Furthermore, "above," "over," and "on top" can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.
[0080] In the embodiments of this disclosure, the same reference numerals denote the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments. It should be understood that the thickness, length, width, and other dimensions of various components in the embodiments of this disclosure shown in the accompanying drawings, as well as the overall thickness, length, width, and other dimensions of the integrated device, are merely illustrative and should not constitute any limitation on this disclosure.
[0081] The "range" disclosed in this disclosure is defined by a lower limit and an upper limit, whereby a given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also expected. Furthermore, if minimum range values 1 and 2 are listed, and if maximum range values 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this disclosure, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0082] Unless otherwise specified, all steps in this disclosure may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0083] Unless otherwise specified, in this disclosure, the terms "first," "second," etc., are used to distinguish different objects, rather than to describe a specific order or primary / secondary relationship.
[0084] In this disclosure, the terms "multiple" or "a variety" refer to two or more kinds.
[0085] Unless otherwise stated, the test temperature for all parameters mentioned in this disclosure is 25°C.
[0086] Cylindrical battery cells can be rechargeable batteries, which are battery cells that can be recharged after discharge to activate the active materials and continue to be used.
[0087] A battery device can refer to a single physical module comprising one or more cylindrical battery cells to provide higher voltage and capacity.
[0088] A cylindrical battery cell includes a casing and an electrode assembly, with the electrode assembly housed within the casing. The electrode assembly includes a positive electrode and a negative electrode. During the charging and discharging process of the cylindrical battery cell, lithium ions repeatedly insert and extract between the positive and negative electrode plates.
[0089] Currently, to obtain high-energy-density cylindrical battery cells, nickel-lithium transition metal oxides are commonly used as the cathode, as they possess a higher voltage plateau and higher theoretical specific capacity, thus providing higher energy density. However, nickel-lithium transition metal oxides have unstable surfaces and strong oxidizing properties, leading to problems with lattice oxygen (O2) during deep delithiation. 2- Gases are more likely to be released as O2, which reacts with the electrolyte to form peroxide intermediates, ultimately producing CO2 and H2O. These gases increase the expansion force inside the cylindrical battery cell, making it risky for the valve to open even before thermal runaway occurs. This can cause the explosion-proof valve to fail, exacerbating the severity of subsequent thermal runaway and affecting the thermal runaway stability of the cylindrical battery cell. Furthermore, these gases also affect the long cycle life of the cylindrical battery cell. The outer casing of cylindrical battery cells is often made of metal, such as steel, which has high structural strength and cannot buffer the expansion caused by gas generation. Additionally, the internal space of cylindrical battery cells is usually small, making the expansion effect of gas generation more pronounced, further increasing the risk of premature valve opening.
[0090] Therefore, existing cylindrical battery cells cannot simultaneously achieve high energy density, long cycle life, and good thermal runaway stability.
[0091] In view of this, this disclosure provides a technical solution that, by adjusting the area ratio of the explosion-proof valve and introducing specific types and amounts of doping elements into the nickel-lithium transition metal oxide, enables cylindrical battery cells to have both high energy density and long cycle life, as well as good thermal runaway stability.
[0092] The cylindrical battery cells described in this disclosure are applicable to battery devices and electrical devices that use cylindrical battery cells or battery devices.
[0093] The electrical devices disclosed in this embodiment can be devices that use cylindrical battery cells or battery devices as power sources, or various energy storage systems that use cylindrical battery cells or battery devices as energy storage elements. Electrical devices can be, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0094] For ease of explanation, the following embodiments will use a vehicle as an example of an electrical device.
[0095] Figure 1 This is a schematic diagram of the structure of a vehicle provided for some embodiments of this disclosure.
[0096] like Figure 1 As shown, a battery device 2 is installed inside the vehicle 1. The battery device 2 can be located at the bottom, front, or rear of the vehicle 1. The battery device 2 can be used to power the vehicle 1; for example, the battery device 2 can serve as the operating power source for the vehicle 1.
[0097] The vehicle 1 may also include a controller 3 and a motor 4. The controller 3 is used to control the battery device 2 to supply power to the motor 4, for example, for the power needs of the vehicle 1 during starting, navigation and driving.
[0098] In some embodiments of this disclosure, the battery device 2 can not only serve as the operating power source for the vehicle 1, but also as the driving power source for the vehicle 1, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1.
[0099] Figure 2 This is a schematic diagram of the structure of a battery device provided in some embodiments of this disclosure.
[0100] In some embodiments, the battery device 2 may include one or more battery cell assemblies for providing voltage and capacity.
[0101] A battery cell assembly may include multiple cylindrical battery cells ( Figure 2 (Not shown) Multiple cylindrical battery cells are connected in series, parallel, or mixed series via a busbar. Mixed series refers to multiple cylindrical battery cells being connected in both series and parallel.
[0102] In some embodiments, the battery cell assembly is typically formed by arranging multiple cylindrical battery cells; as an example, the battery cell assembly can be a battery module 6, which is formed by arranging and fixing multiple cylindrical battery cells to form an independent module.
[0103] In some embodiments, the battery device 2 may be a battery pack, which includes a housing 5 and one or more battery cell assemblies housed within the housing 5. As an example, the battery cell assembly may be a battery module 6, which can be housed within the housing 5 by securing the battery module 6 to the housing. Alternatively, the battery cell assembly may be housed within the housing 5 by directly securing multiple cylindrical battery cells to the housing.
[0104] In some embodiments, the housing 5 is used to house cylindrical battery cells, and the housing 5 can have various structures.
[0105] In some embodiments, the housing 5 may include a first housing 5a and a second housing 5b. The first housing 5a and the second housing 5b are fastened together to form a closed space inside the housing 5 to house the battery cell assembly. Here, "closed" refers to covering or closing, and can be either sealed or unsealed. The first housing may be a top cover or a bottom plate.
[0106] In some embodiments, the housing 5 may include a top cover, a frame, and a bottom plate. The top cover and bottom plate are respectively connected to the frame, forming an enclosed space inside the housing to accommodate individual battery cells. As an example, the frame may include multiple side beams.
[0107] In some embodiments, the housing 5 may be part of the vehicle's chassis structure. For example, a portion of the housing 5 may be at least a portion of the vehicle's floor, or a portion of the housing 5 may be at least a portion of the vehicle's crossbeams and longitudinal beams.
[0108] In some embodiments, the battery device 2 may be an energy storage device.
[0109] Energy storage devices can be used in energy storage power stations, wind power generation systems, solar power generation systems, mobile power systems, or temporary power supply systems. Energy storage devices can store electrical energy as needed and output it when appropriate. For example, energy storage devices can store electrical energy during off-peak hours and provide power to relevant users or electrical devices during peak hours.
[0110] In some embodiments, the energy storage device includes an energy storage container, an energy storage cabinet, etc.
[0111] Figure 3 for Figure 2 The diagram shows the structure of the battery module.
[0112] In some embodiments, such as Figure 3 As shown, there are multiple cylindrical battery cells 7. These multiple cylindrical battery cells 7 are first connected in series, parallel, or in a mixed manner to form a battery module 6. The multiple battery modules 6 are then connected in series, parallel, or in a mixed manner to form a whole, which is housed in the casing 5.
[0113] Multiple cylindrical battery cells 7 in battery module 6 can be electrically connected through busbars to achieve parallel, series, or mixed connection of multiple cylindrical battery cells 7 in battery module 6. There can be one or more busbars, each used to electrically connect at least two cylindrical battery cells 7.
[0114] Figure 4 This is a schematic diagram of the structure of a cylindrical battery cell provided in some embodiments of this disclosure; Figure 5 for Figure 4 The diagram shows an exploded view of a cylindrical battery cell.
[0115] like Figure 4 and Figure 5 As shown, the cylindrical battery cell 7 includes a housing 20 and an electrode assembly 10, with the electrode assembly 10 housed within the housing 20.
[0116] The outer casing 20 is a hollow structure, and its interior forms a space for accommodating the electrode assembly 10 and the electrolyte. The outer casing 20 of the cylindrical battery cell 7 is a cylindrical outer casing.
[0117] As an example, the housing 20 includes a housing 21 and an end cap 22, the housing 21 having an opening and the end cap 22 for closing the opening.
[0118] The housing 21 is a component used to fit the end cap 22 to form the internal cavity of the cylindrical battery cell 7. The formed internal cavity can be used to accommodate the electrode assembly 10, electrolyte, and other components.
[0119] The housing 21 and the end cap 22 can be separate components. For example, an opening can be provided on the housing 21, and the end cap 22 can be used to close the opening to form an internal cavity for the cylindrical battery cell 7.
[0120] The shape of the end cap 22 can be adapted to the shape of the housing 21 to fit the housing 21. The material of the end cap 22 can be the same as or different from the material of the housing 21.
[0121] The end cap 22 is connected to the housing 21 by welding, bonding, snap-fitting or other means.
[0122] The housing 21 may be open at one end or open at both ends. In some examples, the housing 21 may be a structure with an opening on one side, and one end cap 22 is provided to cover the housing 21. In other examples, the housing 21 may also be a structure with openings on both sides, and two end caps 22 are provided, with the two end caps 22 respectively covering the two openings of the housing 21.
[0123] Electrode assembly 10 is the component in the cylindrical battery cell 7 where the electrochemical reaction occurs.
[0124] The electrode assembly 10 includes a positive electrode and a negative electrode. During the charging and discharging process of the cylindrical battery cell, lithium ions are inserted and extracted back and forth between the positive and negative electrode.
[0125] The positive electrode includes a positive current collector and a positive electrode film, the positive electrode film including a positive active material. As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film is disposed on either or both of the two opposite surfaces of the positive current collector.
[0126] In some embodiments, the positive electrode film layer further includes a positive electrode conductive agent. As an example, the positive electrode conductive agent includes, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0127] In some embodiments, the positive electrode film layer further includes a positive electrode binder. As examples, the positive electrode binder includes, but is not limited to, one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins.
[0128] In some embodiments, the positive current collector may be a metal foil or a composite current collector. An example of a metal foil is aluminum foil. The composite current collector includes a polymeric material substrate and a metal material layer formed on at least one surface of the polymeric material substrate. Examples of metal materials include, but are not limited to, one or more of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. Examples of polymeric material substrates include, but are not limited to, one or more of polypropylene, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene, and polyethylene.
[0129] The positive electrode film is typically formed by coating a positive electrode slurry onto a positive electrode current collector, followed by drying and cold pressing. The positive electrode slurry is usually formed by dispersing positive electrode active materials, positive electrode conductive agents, positive electrode binders, and any other components in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP), but is not limited to this.
[0130] The negative electrode sheet includes a negative current collector and a negative electrode film layer, the negative electrode film layer including a negative electrode active material. As an example, the negative current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative current collector.
[0131] In some embodiments, the negative electrode film layer further includes a negative electrode conductive agent. As an example, the negative electrode conductive agent includes, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0132] In some embodiments, the negative electrode film layer includes a negative electrode binder. As an example, the negative electrode binder includes, but is not limited to, one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, waterborne acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0133] In some embodiments, the negative electrode film layer further includes other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, etc.
[0134] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymeric material substrate and a metal material layer formed on at least one surface of the polymeric material substrate. As an example, the metal material may include, but is not limited to, one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymeric material substrate may include, but is not limited to, one or more of polypropylene, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene, and polyethylene.
[0135] The negative electrode film is typically formed by coating a negative electrode slurry onto a negative electrode current collector, followed by drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, negative electrode conductive agent, negative electrode binder, and other optional additives in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited to these.
[0136] like Figure 5 As shown, in some embodiments, the positive current collector includes a positive electrode tab 1111, and the negative current collector includes a negative electrode tab 1211. As an example, the positive electrode tab 1111 is not covered by a positive electrode film layer, and the negative electrode tab 1211 is not covered by a negative electrode film layer.
[0137] Along the axial direction Z of the cylindrical battery cell 7, the positive electrode tab 1111 and the negative electrode tab 1211 can be disposed at the same end of the electrode assembly 10, or they can be disposed at opposite ends of the electrode assembly 10.
[0138] In some embodiments, the positive electrode tab 1111 is disposed at one end of the electrode assembly 10 facing the end wall 211, and the negative electrode tab 1211 is disposed at one end of the electrode assembly 10 facing the end cap 22.
[0139] In some embodiments, the positive electrode tab 1111 is wound into multiple turns. Optionally, the positive electrode tab 1111 is formed into a cylindrical structure by a flattening or smoothing process.
[0140] In some embodiments, the negative electrode tab 1211 is wound into multiple turns. Optionally, the negative electrode tab 1211 is formed into a cylindrical structure by a flattening or smoothing process.
[0141] like Figure 5As shown, in some embodiments, the cylindrical battery cell 7 further includes an electrode terminal 30 disposed on the end wall 211, one of the positive electrode tab 1111 and the negative electrode tab 1211 being electrically connected to the electrode terminal 30, and the other being electrically connected to the end wall 211.
[0142] The end wall 211 and the electrode terminal 30 can serve as two electrodes of the cylindrical battery cell 7 and are located on the same side of the cylindrical battery cell 7. When multiple cylindrical battery cells 7 are assembled into a group, it is convenient to connect the busbar to the end wall 211 or the busbar to the electrode terminal 30, simplifying the structure of the battery device.
[0143] like Figure 5 As shown, the cylindrical battery cell 7 also includes a first current collector 40 and a second current collector 50, which are located on both sides of the electrode assembly 10 along the axial direction Z.
[0144] The first current collector 40 is connected to one of the positive electrode tab 1111 and the negative electrode tab 1211, and the second current collector 50 is connected to the other of the positive electrode tab 1111 and the negative electrode tab 1211.
[0145] The first current collector 40 is connected to the electrode terminal 30, and the second current collector 50 is connected to at least one of the end cap 22 and the side wall 212.
[0146] In some embodiments, the first current collector 40 is connected to the electrode terminal 30 and the positive electrode tab 1111.
[0147] In some embodiments, the second current collector 50 connects the end cap 22 and the negative electrode tab 1211, such that the negative electrode tab 1211 is electrically connected to the end wall 211 through the second current collector 50, the end cap 22, and the side wall 212. In other embodiments, the second current collector 50 is connected to the side wall 212, and the negative electrode tab 1211 is electrically connected to the end wall 211 through the second current collector 50 and the side wall 212; optionally, the end wall 211 is insulated from the side wall 212.
[0148] In some embodiments, the electrode assembly 10 further includes a separator disposed between the positive and negative electrode plates. The separator serves to prevent short circuits between the positive and negative electrodes while allowing lithium ions to pass through. The separator can be a single component located between the positive and negative electrode plates, or it can be attached to the surface of either the positive or negative electrode plate.
[0149] In some embodiments, the cylindrical battery cell 7 further includes an electrolyte contained within the housing 20.
[0150] During the charging and discharging process of the cylindrical battery cell 7, lithium ions are inserted and extracted back and forth between the positive and negative electrode plates, and the electrolyte plays the role of conducting lithium ions between the positive and negative electrode plates.
[0151] In some embodiments, the electrode assembly 10 is a wound structure. Exemplarily, the positive electrode, the separator, and the negative electrode are wound into a cylindrical wound structure along the winding direction.
[0152] In some embodiments, the cylindrical battery cell 7 includes a housing 20, an electrode assembly 10, and an electrolyte. The housing 20 is made of metal, and the electrode assembly 10 and the electrolyte are housed within the housing 20.
[0153] The housing 20 includes a housing 21 and an end cap 22, the housing 21 having an opening and the end cap 22 for closing the opening. The end cap 22 has an explosion-proof valve on its surface, and the explosion-proof valve occupies 10% to 40% of the surface area of the end cap 22; the electrode assembly 10 includes a negative electrode sheet and a positive electrode sheet, the positive electrode sheet includes a positive current collector and a positive electrode film layer, at least one side of the positive current collector is provided with a positive electrode film layer, the positive electrode film layer includes a positive electrode active material, the positive electrode active material includes a nickel-lithium transition metal oxide, the nickel-lithium transition metal oxide includes a modifying element M, M includes one or more of B, Y, Nb, Sn, Zr, Ti, W, Ca, Sr, S, F, Na, K, V, Ta and Mg, the mass percentage of the modifying element M in the positive electrode film layer is 0.01% to 0.4%, and the mass percentage of Ni element is greater than or equal to 50% based on the total mass of transition metals in the nickel-lithium transition metal oxide; the electrolyte includes functional additives, the functional additives include one or more of sulfur-containing additives, boron-containing additives, fluorine-containing additives and carbonate additives, the mass percentage of the functional additives in the electrolyte is 0.05% to 7%.
[0154] Explosion-proof valves, also known as pressure relief valves or safety valves, are core components in the internal safety design of cylindrical battery cells. When a large amount of gas is generated inside a cylindrical battery cell due to thermal runaway or other reasons, causing the pressure to exceed a set threshold, the explosion-proof valve will open before the outer shell of the cylindrical battery cell ruptures, releasing the high-pressure gas and energy internally in a directed manner, thereby mitigating the severity of thermal runaway. The size of the explosion-proof valve affects the intensity of thermal runaway and the timing of valve opening. If the area of the explosion-proof valve is too large, according to the pressure and force area formula, the opening pressure threshold will be higher. At this time, the gas and energy accumulated inside the cylindrical battery cell will be higher, and the gas and energy released at the moment of valve opening will be greater, which will exacerbate the degree of thermal runaway. An excessively large area of the explosion-proof valve will also cause it to withstand excessive pressure, resulting in premature valve opening and reducing long-cycle life. If the area of the explosion-proof valve is too small, it will not be conducive to the smooth discharge of gas and energy inside the cylindrical battery cell when the valve opens, reducing the stability of thermal runaway. The explosion-proof valve disclosed herein has an area ratio of greater than or equal to 10%, which allows the gas and energy inside the cylindrical battery cell to be smoothly discharged during pressure relief, thus mitigating thermal runaway and improving thermal runaway stability. The explosion-proof valve disclosed herein has an area ratio of less than or equal to 40%, which allows the explosion-proof valve to open at a moderate pressure threshold, reducing the risk of premature valve opening and also reducing the intensity of thermal runaway.
[0155] The positive electrode of the cylindrical battery cell disclosed herein comprises a nickel-lithium transition metal oxide, and the mass percentage of Ni element is greater than or equal to 50% based on the total mass of transition metals in the nickel-lithium transition metal oxide. A high mass percentage of Ni element can result in a higher energy density for the cylindrical battery cell. However, a higher mass percentage of Ni element leads to a less stable surface and stronger oxidizing properties of the nickel-lithium transition metal oxide, making it more prone to side reactions with the electrolyte and generating more gas. The modifying elements in the nickel-lithium transition metal oxide of the positive electrode active material disclosed herein can improve the stability of the nickel-lithium transition metal oxide through at least one modification mechanism among TM-site / interstitial doping, anion doping, and Li-site doping, thereby reducing gas generation and improving the cycle life and thermal runaway stability of the cylindrical battery cell. However, the content of the modifying elements affects the modification effect and also the specific capacity of the positive electrode active material. Too many modifying elements result in a low specific capacity of the positive electrode active material and a low energy density of the cylindrical battery cell; too few modifying elements result in a poor modification effect and a higher likelihood of gas generation from the nickel-lithium transition metal oxide. The modified element M disclosed herein has a mass percentage of 0.01% to 0.4% in the positive electrode film layer, which can enable the cylindrical battery cell to have high energy density, long cycle life and thermal runaway stability.
[0156] The content of modifying elements affects the modification effect, and consequently, the gas generation effect. Lower content of modifying elements can result in higher energy density in cylindrical battery cells, but the modification effect is poor, leading to more gas generation. If the area ratio of the explosion-proof valve is too high, the pressure it experiences is excessive, making it prone to premature valve opening and causing valve failure, affecting the cycle performance of the cylindrical battery cell and hindering the control of subsequent thermal runaway stability. Conversely, if the area ratio of the explosion-proof valve is too low, it hinders the smooth discharge of gas and energy from inside the cylindrical battery cell during thermal runaway valve opening, reducing thermal runaway stability. Therefore, the content of modifying elements in this disclosure can work synergistically with the area ratio of the explosion-proof valve to achieve high energy density, long cycle life, and thermal runaway stability in cylindrical battery cells.
[0157] The area of the explosion-proof valve on the end cap surface is 10% to 40%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, or any range of the above values.
[0158] Optionally, the area of the explosion-proof valve on the end cap surface accounts for 10% to 30%.
[0159] The mass percentage of the modified element M in the positive electrode film layer is 0.01% to 0.4%, for example, it can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3%, 0.32%, 0.34%, 0.36%, 0.38%, 0.4%, or any range of the above values.
[0160] Optionally, the mass percentage of the modified element M in the positive electrode film layer is 0.1% to 0.4%.
[0161] Based on the total mass of transition metals in nickel-lithium transition metal oxides, the mass percentage of Ni element is greater than or equal to 50%, greater than or equal to 55%, greater than or equal to 60%, greater than or equal to 65%, greater than or equal to 70%, greater than or equal to 75%, greater than or equal to 80%, greater than or equal to 85%, greater than or equal to 90%, greater than or equal to 95%, or greater than or equal to 98%.
[0162] Optionally, the mass percentage of Ni is 80% to 97% based on the total mass of the transition metals in the nickel-lithium transition metal oxide.
[0163] The mass percentage of Ni in nickel-lithium transition metal oxides can be determined using ICP-OES, based on the total mass of transition metals in the oxide.
[0164] During testing, the positive electrode sheet was removed from the cylindrical battery cell. Approximately 0.4g of dry positive electrode sheet or approximately 1g of moist positive electrode sheet (accurate to 0.0001g) was placed in a 25ml beaker, and 2ml to 5ml of nitric acid was added. The mixture was left overnight and then placed on a hot plate. The mixture was heated at approximately 100℃ until the positive electrode sheet was digested. Then, 0.5ml of perchloric acid was added, and the mixture was heated at approximately 140℃ until the white fumes ceased. The residue should be white; otherwise, nitric acid and perchloric acid should be added again for repeated digestion. Finally, the residue was dissolved and extracted with 7% (volume fraction) hydrochloric acid. The volume was adjusted to an appropriate level based on the content of the element to be tested, and then ICP-OES was used for testing.
[0165] In some embodiments, the explosion-proof valve accounts for 20% to 30% of the area on the end cap surface, the modified element M accounts for 0.25% to 0.4% of the mass in the positive electrode film layer, and the Ni element accounts for 85% to 92% of the mass based on the total mass of the transition metal in the nickel-lithium transition metal oxide.
[0166] The content of modifying elements affects the modification effect, and consequently, the gas generation effect. Lower content of modifying elements can result in higher energy density in cylindrical battery cells, but the modification effect is poor, leading to more gas generation. If the area ratio of the explosion-proof valve is too high, the pressure it experiences is excessive, making it prone to premature valve opening and causing valve failure, affecting the cycle performance of the cylindrical battery cell and hindering the control of subsequent thermal runaway stability. Conversely, if the area ratio of the explosion-proof valve is too low, it hinders the smooth discharge of gas and energy from inside the cylindrical battery cell during thermal runaway valve opening, reducing thermal runaway stability. Therefore, the content of modifying elements in this disclosure can work synergistically with the area ratio of the explosion-proof valve to achieve high energy density, long cycle life, and thermal runaway stability in cylindrical battery cells.
[0167] In some embodiments, when the modifying element M is one or more of B, Y, Nb, Sn, Zr, Ti, W, Sr, V and Ta, the mass percentage of the modifying element M in the positive electrode film layer is 0.03% to 0.2%.
[0168] The surface instability of nickel-lithium transition metal oxides mainly originates from Li / Ni hybridization and Ni 4+ High oxidizing power, Li / Ni mixing leads to oxygen release, Ni 4+The modified element M itself has high oxidizing properties and can also undergo side reactions with the electrolyte. Introducing the aforementioned element M into nickel-lithium transition metal oxides can reduce Li / Ni mixing, reduce lattice distortion, stabilize the layered structure of the nickel-lithium transition metal oxide, and improve the cycle stability of the nickel-lithium transition metal oxide. This, in turn, can reduce side reactions between the nickel-lithium transition metal oxide and the electrolyte, and reduce gas production. A high total mass percentage of the modified element M will reduce the specific capacity of the nickel-lithium transition metal oxide, affecting the energy density of the cylindrical battery cell. In this disclosure, when the modified element M is one or more of B, Y, Nb, Sn, Zr, Ti, W, Sr, V, and Ta, the mass percentage of the modified element M in the positive electrode film is 0.03% to 0.2%. This not only enables the nickel-lithium transition metal oxide to have a high specific capacity but also improves its surface stability, reduces side reactions between the nickel-lithium transition metal oxide and the electrolyte, and reduces gas production. Therefore, the cylindrical battery cell can possess both high energy density and long cycle life.
[0169] In some embodiments, when the modifying element M is one or more of S and F, the mass percentage of the modifying element M in the positive electrode film layer is 0.02% to 0.1%.
[0170] S and F can form stronger chemical bonds with O, more firmly locking in surrounding O elements. This helps reduce oxygen release from nickel-lithium transition metal oxides (LiMeTOs), thereby reducing side reactions between LiMeTOs and the electrolyte and decreasing gas production. A high total mass percentage of the modified element M reduces the specific capacity of LiMeTOs and affects the energy density of the cylindrical battery cell. In this disclosure, when the modified element M is one or more of S and F, its mass percentage in the positive electrode film is 0.02% to 0.1%. This allows the LiMeTO to have a high specific capacity while reducing oxygen release, side reactions, and gas production, thus enabling the cylindrical battery cell to achieve both high energy density and long cycle life.
[0171] In some embodiments, when the modifying element M is one or more of Mg, Na, K and Ca, the mass percentage of the modifying element M in the positive electrode film layer is 0.05% to 0.2%.
[0172] At high SOC (State of Charge), a large portion of the lithium layer is hollowed out, and the interlayer structure is maintained only by weak O-O repulsive forces, making it extremely prone to collapse. Mg² + Na + K + Ca² +Due to their stable valence state and non-ejection characteristics, ions can act like "pillars" within the lithium layer, reducing the likelihood of irreversible collapse of the layered structure along the c-axis, thereby improving the stability of the cathode active material at high SOC. A high total mass percentage of the modifying element M reduces the specific capacity of the nickel-lithium transition metal oxide, affecting the energy density of the cylindrical battery cell. In this disclosure, when the modifying element M is one or more of Mg, Na, K, and Ca, its mass percentage in the cathode film is 0.05% to 0.2%. This not only enables the nickel-lithium transition metal oxide to have a high specific capacity but also improves its stability at high SOC, reduces side reactions between the nickel-lithium transition metal oxide and the electrolyte, and reduces gas production. Therefore, the cylindrical battery cell can achieve both high energy density and long cycle life.
[0173] In some embodiments, the nickel-lithium transition metal oxide particles include an inner region and an outer region. The outer region refers to the area from the outer surface of the particle to a depth of 500 nm in the direction toward the geometric center of the particle. The outer region surrounds the outer periphery of the inner region. Both the inner region and the outer region are provided with the modifying element M.
[0174] The mass percentage of the modified element M in the positive electrode film and the mass ratio of each element in the nickel-lithium transition metal oxide can be tested using ICP-OES.
[0175] During testing, the positive electrode sheet was removed from the cylindrical battery cell. Approximately 0.4g of dry positive electrode sheet or approximately 1g of moist positive electrode sheet (accurate to 0.0001g) was placed in a 25ml beaker, and 2ml to 5ml of nitric acid was added. The mixture was left overnight and then placed on a hot plate. The mixture was heated at approximately 100℃ until the positive electrode sheet was digested. Then, 0.5ml of perchloric acid was added, and the mixture was heated at approximately 140℃ until the white fumes ceased. The residue should be white; otherwise, nitric acid and perchloric acid should be added again for repeated digestion. Finally, the residue was dissolved and extracted with 7% (volume fraction) hydrochloric acid. The volume was adjusted to an appropriate level based on the content of the element to be tested, and then ICP-OES was used for testing.
[0176] In some embodiments, the positive electrode active material includes a nickel-lithium transition metal oxide matrix and a coating layer disposed on at least a portion of the surface of the nickel-lithium transition metal oxide matrix, the coating layer including one or more of cobalt oxide and aluminum oxide.
[0177] The coating layer disclosed herein can serve as a dense physical isolation layer, preventing direct contact between the electrolyte and the positive electrode active material, thereby reducing side reactions between the positive electrode active material and the electrolyte, reducing gas production, and improving the long cycle life of cylindrical battery cells.
[0178] In some embodiments, the Dv50 of the positive electrode active material is from 1 μm to 5 μm. For example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any range of the above values.
[0179] The density (Dv50) of the positive electrode active material can affect the compaction density of the positive electrode film and its reactivity with the electrolyte. A Dv50 greater than or equal to 1 μm results in a lower specific surface area, reducing active sites prone to side reactions with the electrolyte and minimizing gas production. Conversely, a Dv50 less than or equal to 5 μm allows for a higher compaction density, increasing the energy density of the cylindrical battery cell. This, in turn, improves the cycle life and energy density of the cylindrical battery cell.
[0180] Optionally, the Dv50 of the positive electrode active material is 1.5 μm to 4 μm.
[0181] Dv50 represents the particle size corresponding to a cumulative volumetric distribution percentage of 50% for the material. It can be measured using a laser particle size analyzer, referring to GB / T19077-2016. During testing, add 1g of the sample to a clean small beaker and 20ml of deionized water. Sonicate at 53kHz / 120W for 5 minutes to ensure complete dispersion. Turn on the laser particle size analyzer, clean the optical path system, and automatically test the background. Stir the sonicated solution to ensure uniform dispersion, place it in the sample cell as required, and begin measuring the particle size. A MasterSizer 3000 laser particle size analyzer can be used as the testing instrument.
[0182] In some embodiments, the positive electrode active material includes single-crystal particles and polycrystalline particles, with the polycrystalline particles accounting for 50% to 90% of the area in the positive electrode film layer. For example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or any range of the above values.
[0183] This can reduce the amount of fresh interface exposed by cracking of the positive electrode active material, reduce the contact area between the positive electrode active material and the electrolyte, and reduce side reactions. On the other hand, it can give full play to the advantages of high specific capacity, good cycle performance and good kinetic performance of nickel-containing lithium transition metal oxide particles with high nickel content and polycrystalline morphology. Thus, cylindrical battery cells can have both high energy density and good cycle performance.
[0184] The area ratio of polycrystalline particles in the cathode film can be measured using ion polishing cross-sectional morphology analysis (CP) combined with scanning electron microscopy (SEM). SEM images of the cathode film are obtained using CP and SEM. Multiple test areas (e.g., 5) are randomly selected, and at a certain magnification (e.g., 500x or higher), the sum of the areas of all polycrystalline particles in each test area is calculated. The ratio of the sum of the polycrystalline particle areas to the area of the cathode film is the area ratio of polycrystalline particles in the cathode film.
[0185] The terms "single-crystal particle" and "polycrystalline particle" are both well-known in the art. "Single-crystal particle" also includes quasi-single-crystal (also known as near-single-crystal) particles, a well-known term in the art, typically referring to particles composed of a small number, for example, less than 10 primary particles. Typically, the primary particles constituting quasi-single-crystal (near-single-crystal) particles have a particle size greater than 500 nm. Polycrystalline particles refer to secondary particles composed of a large number of nanoscale primary particles. "Single-crystal particle" and "polycrystalline particle" can be distinguished using scanning electron microscopy.
[0186] In some embodiments, the molar percentage of Ni in the transition metal elements of the nickel-lithium transition metal oxide is above 85%.
[0187] Ni has a high molar percentage in transition metals in nickel-lithium transition metal oxides, which can give cylindrical battery cells higher energy density.
[0188] In some embodiments, the nickel-lithium transition metal oxide further includes the general formula Li a Ni b A c O e The nickel-lithium transition metal oxide matrix, wherein 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 1≤e≤2, and A includes one or more of Mn, Al and Co.
[0189] In some embodiments, the nickel-lithium transition metal oxide is a layered positive electrode active material.
[0190] In some embodiments, the reversible specific capacity of the nickel-lithium transition metal oxide is from 200 mAh / g to 225 mAh / g. For example, it can be 200 mAh / g, 205 mAh / g, 210 mAh / g, 215 mAh / g, 220 mAh / g, 225 mAh / g, or any range of the above values.
[0191] The specific capacity of nickel-lithium transition metal oxides can be tested using the following method.
[0192] Disassemble the positive electrode from the cylindrical battery cell, take the positive electrode with single-sided coating (if it is double-sided coated, wipe off the positive electrode film layer on one side first), and assemble it with the lithium sheet in a glove box to form a button cell. Let it stand for 3 hours, and then test it with Blue Electric equipment. The test procedure is as follows: let it stand for 5 minutes, charge it to 4.3V with a constant current of 0.1C, then charge it to 50μA with a constant voltage, let it stand for 5 minutes, and discharge it to 2.5V with a constant current of 0.1C. Cycle 2 times, and take the ratio of the discharge capacity of the second cycle to the mass of the nickel-lithium transition metal oxide, which is the specific capacity of the nickel-lithium transition metal oxide.
[0193] In some embodiments, the negative electrode sheet includes a negative current collector and a negative electrode film layer. The negative current collector has a negative electrode film layer on at least one side. The negative electrode film layer includes a negative electrode active material, which includes one or more of silicon-based materials and carbon-based materials.
[0194] In some embodiments, the carbon-based material includes one or more of artificial graphite, natural graphite, hard carbon, and soft carbon.
[0195] In some embodiments, silicon-based materials include one or more of silicon-carbon materials, elemental silicon, silicon oxides, silicon-nitrogen composites, and silicon alloys.
[0196] In some embodiments, the mass percentage of Si element in the negative electrode film layer is 3% to 20%. For example, it can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or any range of the above values.
[0197] Within this range, the energy density of cylindrical battery cells can be increased, and the negative electrode sheet can have a lower volume expansion. This reduces the risk of premature opening of the explosion-proof valve caused by the volume expansion of the negative electrode, thus giving the cylindrical battery cells good thermal runaway stability.
[0198] The mass percentage of Si in the negative electrode film can be measured using an inductively coupled plasma optical emission spectrometer (ICP). The testing standard can be found in JY / T 015-1996.
[0199] In some embodiments, the silicon-based material includes a silicon-carbon material, which includes a porous carbon substrate and silicon located in the pores of the porous carbon substrate.
[0200] The porosity of the porous carbon substrate can reduce the volume expansion of silicon, thereby reducing the risk of premature opening of the explosion-proof valve caused by the volume expansion of the negative electrode, and enabling the cylindrical battery cell to have good thermal runaway stability.
[0201] In some embodiments, the negative electrode film layer includes a first film layer away from the negative electrode current collector and a second film layer close to the negative electrode current collector. The first film layer includes a silicon-based material and a carbon-based material, and the second film layer includes a carbon-based material. The silicon-based material further includes an alkali metal element and / or an alkaline earth metal element, and the mass percentage of silicon element in the silicon-based material is 2% to 70%. For example, it can be 2%, 5%, 10%, 12%, 15%, 17%, 20%, 22%, 25%, 27%, 30%, 32%, 35%, 37%, 40%, 42%, 45%, 47%, 50%, 52%, 55%, 57%, 60%, 62%, 65%, 67%, 70%, or any range of the above values.
[0202] The first film layer is located away from the negative electrode current collector, and the second film layer is located close to the negative electrode current collector, forming a structure in which the first film layer, the second film layer, and the negative electrode current collector are stacked sequentially. In this case, the second film layer is positioned between the first film layer and the negative electrode current collector. Carbon-based materials have lower volume expansion than silicon-based materials. Therefore, including a carbon-based material in the second film layer close to the negative electrode current collector can reduce the compression of the negative electrode current collector by the volume expansion of the negative electrode active material, reduce the risk of active film layer detachment, and improve the long cycle life of the cylindrical battery cell. Including a silicon-based material in the first film layer can increase the energy density of the cylindrical battery cell; however, the large volume expansion of silicon-based materials can affect the cycle stability of the negative electrode. Therefore, the silicon-based material also includes alkali metal elements and / or alkaline earth metal elements, which can reduce the volume expansion of the silicon material; at the same time, the mass percentage of silicon in the silicon-based material is 2% to 70%, which can balance high energy density and low volume expansion. This can improve the energy density and long cycle life of the cylindrical battery cell.
[0203] Optionally, the alkali metal element is Li, and the alkaline earth metal element is Mg.
[0204] Optionally, silicon-based materials include pre-magnesium silicate materials.
[0205] Optionally, the silicon element in the silicon-based material accounts for 2% to 20% by mass.
[0206] The silicon content of different films on the negative electrode side can be determined using instruments and methods known in the art. It can be tested using ion-polished cross-sectional morphology (CP) images and energy dispersive spectroscopy (EDS). For example, a cylindrical battery cell can be disassembled to obtain the negative electrode sheet. The microstructure of the complete cross-section of the negative electrode sheet can be observed to obtain a CP image. The boundary between the first and second films can be identified based on the obvious discontinuous changes in the microstructure in the CP image. Subsequently, EDS compositional analysis can be used to identify the elemental types in the CP image to confirm the composition of the first or second film layer, thereby obtaining the mass content of silicon in the first or second film layer.
[0207] In some embodiments, the electrolyte includes functional additives, which include one or more of sulfur-containing additives, boron-containing additives, fluorine-containing additives, and carbonate additives. The functional additives account for 0.05% to 7% of the electrolyte by mass. For example, they can be 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, or any range of the above values.
[0208] During charging and discharging, the nickel-lithium transition metal oxide (CDI) cathode active material undergoes side reactions with the electrolyte, generating gas and simultaneously forming a CEI film on its surface. However, the CEI film in existing cylindrical battery cells is structurally unstable and has poor mechanical toughness, leading to rupture or decomposition during charging and discharging. This exposes new active surfaces of the nickel-lithium transition metal oxide, further exacerbating the side reactions and increasing gas production.
[0209] This disclosure introduces the aforementioned functional additives into the electrolyte, which can form a denser and more oxidation-resistant CEI film, thereby reducing gas production. However, if too many functional additives are used, they will continue to react and accumulate on the surface of nickel-lithium transition metal oxides to form an excessively thick CEI film, severely hindering lithium-ion transport, leading to a significant increase in battery polarization and affecting the long cycle life of the cylindrical battery cell. If too few functional additives are used, the CEI film is not dense enough and has weak oxidation resistance, increasing gas production. The electrolyte in the embodiments of this disclosure includes functional additives, which include one or more of sulfur-containing additives, boron-containing additives, fluorine-containing additives, and carbonate additives. The functional additives account for 0.05% to 7% of the mass of the electrolyte, which can enable the cylindrical battery cell to have a long cycle life.
[0210] In some embodiments, the sulfur-containing additive includes one or more of 1,3-propenesulfonate lactone, vinyl sulfate, and vinyl sulfite.
[0211] In some embodiments, the boron-containing additive includes one or more of lithium difluorophosphate and lithium bis(oxalato)borate.
[0212] In some embodiments, the fluorinated additives include one or more of fluoroethylene carbonate, lithium difluorooxalate borate, and lithium difluorophosphate.
[0213] In some embodiments, carbonate additives include one or more of dimethyl carbonate, ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate.
[0214] In some embodiments, the electrolyte further includes an electrolyte salt, which includes one or more of lithium hexafluorophosphate, lithium difluorophosphate, and lithium bis(oxalato)borate.
[0215] In some embodiments, the molar concentration of the electrolyte salt is from 0.7 mol / L to 1.5 mol / L. For example, it can be 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, or any range of the above values.
[0216] When the molar concentration of the electrolyte salt is within the above range, it is beneficial to further improve the stability of the electrolyte salt and to improve the conductivity and ion migration rate of the electrolyte, thereby improving the cycle performance of the cylindrical battery cell.
[0217] In some embodiments, the electrode assembly further includes a separator membrane located between the positive electrode and the negative electrode. The separator membrane includes a base film and a coating located on at least one side of the base film. The coating includes a first coating away from the base film and a second coating close to the base film. The first coating includes ceramic particles, and the second coating includes polymer particles.
[0218] The first coating is located away from the base film, and the second coating is located close to the base film, forming a structure in which the first coating, the second coating, and the base film are stacked sequentially. The second coating is positioned between the first coating and the base film. The first coating includes ceramic particles, which can form a high-temperature resistant layer, allowing the separator to still function as a barrier between the positive and negative electrodes during thermal runaway, thus improving the stability of the cylindrical battery cell. The second film layer includes polymer particles, which can improve the adhesion between the coating and the base film, reduce the risk of coating detachment, and further improve the stability of the cylindrical battery cell.
[0219] This disclosure does not impose any particular limitation on the base film of the separator. As an example, the base film of the separator may be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, polyvinylidene fluoride, and ceramic. The separator may be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0220] In some embodiments, the outer diameter of the housing 20 is 30 mm to 80 mm, for example, it can be 30 mm, 35 mm, 40 mm, 45 mm, 50 mm, 55 mm, 60 mm, 65 mm, 70 mm, 75 mm, 80 mm, or any range of the above values. The outer diameter refers to the outer diameter of the housing 20.
[0221] Setting the outer diameter of the casing 20 to be greater than or equal to 30 mm can increase the capacity and energy density of the cylindrical battery cell 7. Setting the outer diameter of the casing 20 to be less than or equal to 80 mm can reduce the risk of the casing 20 cracking due to the expansion of the electrode assembly 10, thereby improving the reliability of the cylindrical battery cell 7.
[0222] Optionally, the outer diameter of the housing 20 is 40 mm to 60 mm.
[0223] In some embodiments, the dimension of the housing 20 along the axial direction Z of the cylindrical battery cell 7 is 50mm to 150mm, for example, it can be 50mm, 55mm, 60mm, 65mm, 70mm, 75mm, 80mm, 85mm, 90mm, 95mm, 100mm, 105mm, 110mm, 115mm, 120mm, 125mm, 130mm, 135mm, 140mm, 145mm, 150mm, or any range of the above values.
[0224] Setting the dimension of the cylindrical battery cell 7 along the axial direction Z to be greater than or equal to 50 mm can improve the capacity and energy density of the cylindrical battery cell 7. Setting the dimension of the cylindrical battery cell 7 along the axial direction Z to be less than or equal to 150 mm can reduce the difficulty of electrolyte wetting into the middle region of the electrode assembly 10 and improve the electrolyte wettability of the electrode assembly 10.
[0225] Optionally, the housing 20 has a dimension of 70 mm to 100 mm along the axial direction Z of the cylindrical battery cell 7.
[0226] In some embodiments, the outer diameter of the housing 20 is 30 mm to 80 mm, and the axial dimension Z of the housing 20 along the cylindrical battery cell 7 is 50 mm to 150 mm. When the housing 20 meets the above dimensional requirements, it has high structural stability and can improve the reliability of the cylindrical battery cell 7.
[0227] In some embodiments, the housing 20 includes a housing 21 and an end cap 22. The housing 21 includes a sidewall 212 and an end wall 211 connected to the sidewall 212, the sidewall 212 surrounding the electrode assembly 10. As an example, the sidewall 212 is cylindrical. The housing 21 has an opening, the end cap 22 is connected to the sidewall 212 and closes the opening, and the end cap 22 and the end wall 211 are opposite each other along the axial direction Z of the cylindrical battery cell 7.
[0228] In some embodiments, the base material of the sidewall 212 is steel. The base material of the sidewall 212 refers to the material that accounts for the largest proportion of the mass in the sidewall 212.
[0229] Steel has high mechanical strength. Using steel sidewalls 212 can improve the structural stability of sidewalls 212, reduce the deformation of sidewalls 212, and improve the reliability of cylindrical battery cells 7.
[0230] In some embodiments, the base material of the sidewall 212 is stainless steel.
[0231] In some embodiments, the sidewall 212 includes a sidewall body and a protective layer disposed inside the sidewall body. The sidewall body is made of steel, and the base element of the protective layer is nickel. Nickel can improve the acid corrosion resistance to friction.
[0232] As an example, the nickel content in the protective layer is 70% to 100% by mass, and can be 80% to 95%.
[0233] In some embodiments, the base material of the sidewall 212 is steel, and the thickness of the sidewall 212 is 0.2 mm to 0.6 mm, for example, it can be 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm, 0.6 mm, or any range of the above values.
[0234] The thickness of the sidewall 212 is set to be greater than or equal to 0.2 mm to improve the mechanical strength of the sidewall 212, reduce the deformation of the sidewall 212 when the electrode assembly 10 expands, reduce the risk of the sidewall 212 breaking, and improve the reliability of the cylindrical battery cell 7. The thickness of the sidewall 212 is set to be less than or equal to 0.6 mm to reduce the mass proportion of the sidewall 212 in the cylindrical battery cell 7 and increase the energy density of the cylindrical battery cell 7.
[0235] Optionally, the thickness of the sidewall 212 is 0.3 mm to 0.5 mm, or 0.35 mm to 0.45 mm.
[0236] The thickness of the sidewall can be measured using a micrometer or vernier caliper.
[0237] In some embodiments, the dimension of the housing 20 along the axial direction Z of the cylindrical battery cell 7 is 1.3 to 2.6 times the outer diameter of the housing 20, for example, it can be 1.3 times, 1.5 times, 1.7 times, 1.9 times, 2.1 times, 2.3 times, 2.6 times, or any range of the above values. When the housing 20 meets the above dimensional requirements, it can effectively constrain the volume expansion of the electrode assembly 10, making the compressive force on the housing 20 more evenly distributed, and the housing 20 is less prone to deformation, thereby improving the reliability of the cylindrical battery cell 7.
[0238] Example 1 Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0239] The positive electrode active material particles are made of LiNiO. 87 Co 0.115 Al 0.015 O2 is obtained by doping the matrix with Ca, F, B, and Zr elements. Based on LiNiO. 87 Co 0.115 Al 0.015 In O2, the total mass of transition metals Ni, Co, and Al is 87%, while in the positive electrode film, the mass percentages of Ca, F, B, and Zr are 0.35%.
[0240] Preparation of negative electrode sheet Artificial graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. After thorough mixing, a negative electrode slurry was prepared. The negative electrode slurry was then uniformly coated onto both surfaces of a copper foil current collector. After drying, cold pressing, and slitting, the negative electrode sheet was obtained. The negative electrode sheet consists of a negative current collector and a negative electrode film layer, with the negative electrode film layer located on both sides of the negative current collector.
[0241] Preparation of the separating membrane A composite slurry of alumina and polyvinylidene fluoride (PVDF) was coated on both sides of a porous polyethylene (PE) polymer film, and the resulting membrane was dried to obtain a release film. The coating weight of the slurry on one side (excluding solvent) was 2.21 g / m². 2 .
[0242] Preparation of electrolyte The electrolyte comprises an organic solvent, a lithium salt, and functional additives. The organic solvent includes carbonate solvents, specifically ethylene carbonate and ethyl methyl carbonate, with ethylene carbonate comprising 40% and ethyl methyl carbonate comprising 60% by mass. The lithium salt includes lithium hexafluorophosphate (LiPF6). The functional additives include fluoroethylene carbonate (FEC), 1,3-propenesulfonyl lactone (1,3-PS), lithium difluorophosphate (LiPO2F2), and lithium bis(oxalato)borate (LiBOB). Ethyl carbonate and ethyl methyl carbonate are mixed according to the above mass ratio. Then, the thoroughly dried lithium salt is dissolved in the mixed organic solvent, and the functional additives are added to prepare the electrolyte. The molar concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L. The functional additives constitute 3% of the electrolyte by mass, specifically 0.5% of FEC, 0.5% of 1,3-PS, 1% of LiPO2F2, and 1% of LiBOB.
[0243] Preparation of cylindrical battery cells The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes. The positive electrode, separator, and negative electrode are then wound to form an electrode assembly. This assembly is placed in a cylindrical outer shell, dried, and then injected with electrolyte. After settling and formation processes, a cylindrical battery cell is obtained. The outer shell includes a housing and end caps. The housing includes integrally formed sidewalls and end walls. The sidewalls surround the electrode assembly, and the end caps and end walls are axially opposite each other along the housing. The sidewalls are made of nickel-plated steel. An explosion-proof valve is provided on the end cap, occupying 25% of the end cap's area.
[0244] Comparative Example 1 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0245] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0246] The positive electrode active material particles are LiNi0. 87 Co 0.115 Al 0.015O2.
[0247] Comparative Example 2 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0248] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0249] The positive electrode active material particles are made of LiNiO. 45 Co 0.35 Al 0.25 O2 is obtained by doping the matrix with Ca, F, B, and Zr elements. Based on LiNiO. 45 Co 0.35 Al 0.25 In O2, the total mass of transition metals Ni, Co, and Al is 45%, while in the positive electrode film, the mass percentages of Ca, F, B, and Zr are 0.35%.
[0250] Performance testing (1) Energy density test of cylindrical battery cells At 25°C, a cylindrical battery cell is charged at a constant current rate of 1 / 3C to 4.25V, and then charged at a constant voltage rate of 4.25V until the current drops to 0.05C. After resting for 5 minutes, the cylindrical battery cell is discharged at a constant current rate of 1 / 3C to 2.5V. The total discharge capacity C0 and the total discharge energy E0 are recorded. The ratio of the total discharge energy E0 of the cylindrical battery cell to its volume is the volumetric energy density of the cylindrical battery cell.
[0251] (2) Cycle life test of cylindrical battery cells At 25°C, the cylindrical battery cell is charged at a constant current rate of 0.5C to 4.25V, and then charged at a constant voltage rate of 4.25V until the current drops to 0.05C. After resting for 5 minutes, the cylindrical battery cell is discharged at a constant current rate of 0.5C to 2.5V. This constitutes one charge-discharge cycle, and the capacity at this point is recorded as the capacity of the first cycle. The above charge-discharge cycle steps are repeated, and the capacity after each cycle is recorded until the cycle capacity retention rate (i.e., the ratio of the capacity after the cycle to the capacity of the first cycle) is 80%, and the number of cycles is recorded.
[0252] Table 1
[0253] As shown in Table 1, when the electrolyte, negative electrode composition and explosion-proof valve area ratio are the same, based on the total mass of transition metals in the nickel-lithium transition metal oxide, by making the mass ratio of Ni element greater than or equal to 50% and including a specific amount of modified element M in the nickel-lithium transition metal oxide in the positive electrode film, cylindrical battery cells can have both high energy density and long cycle life.
[0254] In Comparative Example 1, the nickel-lithium transition metal oxide does not contain any doped elements. Its surface is unstable and easily reacts with the electrolyte, resulting in high gas production, easy failure of the explosion-proof valve, and poor cycle performance of the cylindrical battery cells.
[0255] In Comparative Example 2, the nickel-lithium transition metal oxide has a low Ni content, good surface stability, and is not prone to side reactions with the electrolyte, which can give the cylindrical battery cell a long cycle life. However, the specific capacity of the nickel-lithium transition metal oxide is low, and the energy density of the cylindrical battery cell is low, which does not meet the requirements of high energy density.
[0256] Example 1-1 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0257] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0258] The positive electrode active material particles are made of LiNiO. 87Co 0.115 Al 0.015 O2 is obtained by doping the matrix with B and Zr elements. Based on LiNiO. 87 Co 0.115 Al 0.015 In O2, based on the total mass of Ni, Co, and Al, Ni accounts for 87% of the mass; in the positive electrode film, B and Zr each account for 0.35% of the mass.
[0259] Examples 1-2 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0260] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0261] The positive electrode active material particles are made of LiNiO. 87 Co 0.115 Al 0.015 O2 is obtained by doping the matrix with F. Based on LiNiO. 87 Co 0.115 Al 0.015 In O2, based on the total mass of Ni, Co, and Al, Ni accounts for 87% of the mass; in the positive electrode film, F accounts for 0.35% of the mass.
[0262] Examples 1-3 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0263] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2The compaction density (PD) is 3.5 g / cm³. 3 .
[0264] The positive electrode active material particles are made of LiNiO. 87 Co 0.115 Al 0.015 O2 is obtained by doping the matrix with Ca. Based on LiNiO. 87 Co 0.115 Al 0.015 In O2, based on the total mass of Ni, Co, and Al, Ni accounts for 87% of the mass; in the positive electrode film, Ca accounts for 0.35% of the mass.
[0265] Table 2
[0266] As shown in Table 2, different types of modifying element M can improve the energy density and cycle life of cylindrical battery cells.
[0267] Example 2-1 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0268] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0269] The positive electrode active material particles are made of LiNiO. 87 Co 0.115 Al 0.015 O2 is obtained by doping the matrix with Ca, F, B, and Zr elements. Based on LiNiO. 87 Co 0.115 Al 0.015 In O2, based on the total mass of Ni, Co, and Al, Ni accounts for 87% of the mass; in the positive electrode film, B and Zr each account for 0.03% of the mass.
[0270] Example 2-2 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0271] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0272] The positive electrode active material particles are made of LiNiO. 87 Co 0.115 Al 0.015 O2 is obtained by doping the matrix with Ca, F, B, and Zr elements. Based on LiNiO. 87 Co 0.115 Al 0.015 In O2, based on the total mass of Ni, Co, and Al, Ni accounts for 87% of the mass; in the positive electrode film, F accounts for 0.06% of the mass.
[0273] Example 2-3 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0274] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0275] The positive electrode active material particles are made of LiNiO. 87 Co 0.115 Al 0.015 O2 is obtained by doping the matrix with Ca, F, B, and Zr elements. Based on LiNiO. 87 Co 0.115 Al 0.015 In O2, based on the total mass of Ni, Co, and Al, Ni accounts for 87% of the mass; in the positive electrode film, Ca accounts for 0.2% of the mass.
[0276] Table 3
[0277] As shown in Table 3, the mass ratio of the modified element M in the positive electrode film layer can improve the energy density and cycle life of the cylindrical battery cell.
[0278] Example 3-1 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0279] Preparation of cylindrical battery cells The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes. The positive electrode, separator, and negative electrode are then wound to form an electrode assembly. This assembly is placed in a cylindrical outer shell, dried, and then injected with electrolyte. After settling and formation processes, a cylindrical battery cell is obtained. The outer shell includes a housing and end caps. The housing includes integrally formed sidewalls and end walls. The sidewalls surround the electrode assembly, and the end caps and end walls are axially opposite each other along the housing. The sidewalls are made of nickel-plated steel. An explosion-proof valve is provided on the end cap, occupying 10% of the area of the end cap.
[0280] Example 3-2 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0281] Preparation of cylindrical battery cells The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes. The positive electrode, separator, and negative electrode are then wound to form an electrode assembly. This assembly is placed in a cylindrical outer shell, dried, and then injected with electrolyte. After settling and formation processes, a cylindrical battery cell is obtained. The outer shell includes a housing and end caps. The housing includes integrally formed sidewalls and end walls, with the sidewalls surrounding the electrode assembly. The end caps and end walls are axially opposite each other along the housing. The sidewalls are made of nickel-plated steel. An explosion-proof valve is provided on the end cap, occupying 40% of the end cap's area.
[0282] Table 4
[0283] As shown in Table 4, the different area ratios of the explosion-proof valve on the end cap surface can improve the energy density and cycle life of cylindrical battery cells.
[0284] Example 4-1 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0285] Preparation of electrolyte The electrolyte comprises an organic solvent, a lithium salt, and a functional additive. The organic solvent includes carbonate solvents, specifically ethylene carbonate and ethyl methyl carbonate, with ethylene carbonate comprising 40% and ethyl methyl carbonate comprising 60% by mass. The lithium salt is lithium hexafluorophosphate (LiPF6), and the functional additive is fluoroethylene carbonate (FEC). Ethylene carbonate and ethyl methyl carbonate are mixed according to the above mass ratio. Then, the thoroughly dried lithium salt is dissolved in the mixed organic solvent, and the functional additive is added to prepare the electrolyte. The molar concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L, and the functional additive accounts for 0.05% of the electrolyte by mass.
[0286] Example 4-2 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0287] Preparation of electrolyte The electrolyte comprises an organic solvent, a lithium salt, and functional additives. The organic solvent includes carbonate solvents, specifically ethylene carbonate and ethyl methyl carbonate, with ethylene carbonate comprising 40% and ethyl methyl carbonate comprising 60% by mass. The lithium salt comprises lithium hexafluorophosphate (LiPF6), and the functional additives comprise fluoroethylene carbonate (FEC) and 1,3-propenesulfonyl lactone (1,3-PS). Ethyl carbonate and ethyl methyl carbonate are mixed according to the above mass ratio. Then, the thoroughly dried lithium salt is dissolved in the mixed organic solvent, and the functional additives are added to prepare the electrolyte. The molar concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L, and the functional additives comprise 1% by mass, of which FEC comprises 0.5% and 1,3-PS comprises 0.5% by mass.
[0288] Example 4-3 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0289] Preparation of electrolyte The electrolyte comprises an organic solvent, a lithium salt, and functional additives. The organic solvent includes carbonate solvents, specifically ethylene carbonate and ethyl methyl carbonate, with ethylene carbonate comprising 40% and ethyl methyl carbonate comprising 60% by mass. The lithium salt includes lithium hexafluorophosphate (LiPF6). The functional additives include fluoroethylene carbonate (FEC), 1,3-propenesulfonyl lactone (1,3-PS), lithium difluorophosphate (LiPO2F2), and lithium bis(oxalato)borate (LiBOB). Ethyl carbonate and ethyl methyl carbonate are mixed according to the above mass ratio. Then, the thoroughly dried lithium salt is dissolved in the mixed organic solvent, and the functional additives are added to prepare the electrolyte. The molar concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L. The functional additives constitute 7% of the electrolyte by mass, specifically 1.5% of FEC, 1.5% of 1,3-PS, 2% of LiPO2F2, and 2% of LiBOB.
[0290] Table 5
[0291] As shown in Table 5, the different mass proportions of the functional additives disclosed in the electrode solution can improve the energy density and cycle life of cylindrical battery cells.
[0292] Example 5-1 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0293] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0294] The positive electrode active material particles are made of LiNiO. 87 Co 0.115 Al 0.015 O2 is obtained by doping the matrix with Ca, F, B, and Zr elements. Based on LiNiO. 87 Co 0.115 Al 0.015In O2, considering the total mass of transition metals Ni, Co, and Al, Ni accounts for 87% of the mass; in the positive electrode film, Ca, F, B, and Zr each account for 0.35% of the mass. The positive electrode active material particles also include those disposed in LiNiO. 87 Co 0.115 Al 0.015 The coating layer on at least part of the surface of the O2 substrate includes cobalt oxide and aluminum oxide, and the Dv50 of the positive electrode active material is 3 μm.
[0295] Example 5-2 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0296] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0297] The positive electrode active material particles are made of LiNiO. 87 Co 0.115 Al 0.015 O2 is obtained by doping the matrix with Ca, F, B, and Zr elements. Based on LiNiO. 87 Co 0.115 Al 0.015 In O2, considering the total mass of transition metals Ni, Co, and Al, Ni accounts for 87% of the mass; in the positive electrode film, Ca, F, B, and Zr each account for 0.35% of the mass. The positive electrode active material particles also include those disposed in LiNiO. 87 Co 0.115 Al 0.015 The coating layer on at least part of the surface of the O2 substrate includes cobalt oxide, and the Dv50 of the positive electrode active material is 3 μm.
[0298] Example 5-3 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0299] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0300] The positive electrode active material particles are made of LiNiO. 87 Co 0.115 Al 0.015 O2 is obtained by doping the matrix with Ca, F, B, and Zr elements. Based on LiNiO. 87 Co 0.115 Al 0.015 In O2, considering the total mass of transition metals Ni, Co, and Al, Ni accounts for 87% of the mass; in the positive electrode film, Ca, F, B, and Zr each account for 0.35% of the mass. The positive electrode active material particles also include those disposed in LiNiO. 87 Co 0.115 Al 0.015 The coating layer on at least part of the surface of the O2 substrate includes aluminum oxide, and the Dv50 of the positive electrode active material is 3 μm.
[0301] Example 5-4 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0302] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0303] The positive electrode active material particles are made of LiNiO. 87 Co 0.115 Al 0.015O2 is obtained by doping the matrix with Ca, F, B, and Zr elements. Based on LiNiO. 87 Co 0.115 Al 0.015 In O2, considering the total mass of transition metals Ni, Co, and Al, Ni accounts for 87% of the mass; in the positive electrode film, Ca, F, B, and Zr each account for 0.35% of the mass. The positive electrode active material particles also include those disposed in LiNiO. 87 Co 0.115 Al 0.015 The coating layer on at least part of the surface of the O2 substrate includes cobalt oxide and aluminum oxide, and the Dv50 of the positive electrode active material is 1 μm.
[0304] Example 5-5 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0305] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0306] The positive electrode active material particles are made of LiNiO. 87 Co 0.115 Al 0.015 O2 is obtained by doping the matrix with Ca, F, B, and Zr elements. Based on LiNiO. 87 Co 0.115 Al 0.015 In O2, considering the total mass of transition metals Ni, Co, and Al, Ni accounts for 87% of the mass; in the positive electrode film, Ca, F, B, and Zr each account for 0.35% of the mass. The positive electrode active material particles also include those disposed in LiNiO. 87 Co 0.115 Al 0.015 The coating layer on at least part of the surface of the O2 substrate includes cobalt oxide and aluminum oxide, and the Dv50 of the positive electrode active material is 2 μm.
[0307] Examples 5-6 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0308] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0309] The positive electrode active material particles are made of LiNiO. 87 Co 0.115 Al 0.015 O2 is obtained by doping the matrix with Ca, F, B, and Zr elements. Based on LiNiO. 87 Co 0.115 Al 0.015 In O2, considering the total mass of transition metals Ni, Co, and Al, Ni accounts for 87% of the mass; in the positive electrode film, Ca, F, B, and Zr each account for 0.35% of the mass. The positive electrode active material particles also include those disposed in LiNiO. 87 Co 0.115 Al 0.015 The coating layer on at least part of the surface of the O2 substrate includes cobalt oxide and aluminum oxide, and the Dv50 of the positive electrode active material is 4 μm.
[0310] Examples 5-7 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0311] Preparation of positive electrode sheet A positive electrode slurry was prepared by adding positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) to N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 and mixing thoroughly. The positive electrode slurry was then uniformly coated onto both surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode sheet consists of a positive electrode current collector and a positive electrode film layer, with the film layer located on both sides of the current collector. The coating weight (CW) of the positive electrode film layer was 250 mg / 1540.25 mm². 2 The compaction density (PD) is 3.5 g / cm³. 3 .
[0312] The positive electrode active material particles are made of LiNiO. 87 Co 0.115 Al 0.015 O2 is obtained by doping the matrix with Ca, F, B, and Zr elements. Based on LiNiO. 87 Co 0.115 Al 0.015 In O2, considering the total mass of transition metals Ni, Co, and Al, Ni accounts for 87% of the mass; in the positive electrode film, Ca, F, B, and Zr each account for 0.35% of the mass. The positive electrode active material particles also include those disposed in LiNiO. 87 Co 0.115 Al 0.015 The coating layer on at least part of the surface of the O2 substrate includes cobalt oxide and aluminum oxide, and the Dv50 of the positive electrode active material is 5 μm.
[0313] Table 6
[0314] As shown in Table 6, this disclosure improves the energy density and cycle life of cylindrical battery cells by providing a coating layer on at least a portion of the surface of a nickel-lithium transition metal oxide substrate, the coating layer including one or more of cobalt oxide and aluminum oxide, and the Dv50 of the positive electrode active material being 1 μm to 5 μm.
[0315] Example 6-1 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0316] Preparation of negative electrode sheet A first negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the first negative electrode slurry. A second negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the second negative electrode slurry. The first and second negative electrode slurries were simultaneously coated onto both surfaces of the copper foil of the negative electrode current collector at a coating weight ratio (excluding solvent) of 1:1. After drying, cold pressing, and slitting, the negative electrode sheets were obtained. The second negative electrode slurry was placed closer to the negative electrode current collector, and the first negative electrode slurry was placed further away. After drying, the first slurry formed the first negative electrode film layer, and after drying, the second slurry formed the second negative electrode film layer.
[0317] The first negative electrode active material includes pre-magnesium silicon oxide and artificial graphite, with silicon accounting for 35% of the mass of the pre-magnesium silicon oxide.
[0318] The second negative electrode active material includes artificial graphite.
[0319] Example 6-2 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0320] Preparation of negative electrode sheet A first negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the first negative electrode slurry. A second negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the second negative electrode slurry. The first and second negative electrode slurries were simultaneously coated onto both surfaces of the copper foil of the negative electrode current collector at a coating weight ratio (excluding solvent) of 1:1. After drying, cold pressing, and slitting, the negative electrode sheets were obtained. The second negative electrode slurry was placed closer to the negative electrode current collector, and the first negative electrode slurry was placed further away. After drying, the first slurry formed the first negative electrode film layer, and after drying, the second slurry formed the second negative electrode film layer.
[0321] The first negative electrode active material includes pre-magnesium silicon oxide and artificial graphite, with silicon accounting for 2% of the mass of the pre-magnesium silicon oxide.
[0322] The second negative electrode active material includes artificial graphite.
[0323] Example 6-3 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0324] Preparation of negative electrode sheet A first negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the first negative electrode slurry. A second negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the second negative electrode slurry. The first and second negative electrode slurries were simultaneously coated onto both surfaces of the copper foil of the negative electrode current collector at a coating weight ratio (excluding solvent) of 1:1. After drying, cold pressing, and slitting, the negative electrode sheets were obtained. The second negative electrode slurry was placed closer to the negative electrode current collector, and the first negative electrode slurry was placed further away. After drying, the first slurry formed the first negative electrode film layer, and after drying, the second slurry formed the second negative electrode film layer.
[0325] The first negative electrode active material includes pre-magnesium silicon oxide and artificial graphite, with silicon accounting for 10% of the mass of the pre-magnesium silicon oxide.
[0326] The second negative electrode active material includes artificial graphite.
[0327] Example 6-4 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0328] Preparation of negative electrode sheet A first negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the first negative electrode slurry. A second negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the second negative electrode slurry. The first and second negative electrode slurries were simultaneously coated onto both surfaces of the copper foil of the negative electrode current collector at a coating weight ratio (excluding solvent) of 1:1. After drying, cold pressing, and slitting, the negative electrode sheets were obtained. The second negative electrode slurry was placed closer to the negative electrode current collector, and the first negative electrode slurry was placed further away. After drying, the first slurry formed the first negative electrode film layer, and after drying, the second slurry formed the second negative electrode film layer.
[0329] The first negative electrode active material includes pre-magnesium silicon oxide and artificial graphite, with silicon accounting for 20% of the mass of the pre-magnesium silicon oxide.
[0330] The second negative electrode active material includes artificial graphite.
[0331] Example 6-5 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0332] Preparation of negative electrode sheet A first negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the first negative electrode slurry. A second negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the second negative electrode slurry. The first and second negative electrode slurries were simultaneously coated onto both surfaces of the copper foil of the negative electrode current collector at a coating weight ratio (excluding solvent) of 1:1. After drying, cold pressing, and slitting, the negative electrode sheets were obtained. The second negative electrode slurry was placed closer to the negative electrode current collector, and the first negative electrode slurry was placed further away. After drying, the first slurry formed the first negative electrode film layer, and after drying, the second slurry formed the second negative electrode film layer.
[0333] The first negative electrode active material includes pre-magnesium silicon oxide and artificial graphite, with silicon accounting for 30% of the mass of the pre-magnesium silicon oxide.
[0334] The second negative electrode active material includes artificial graphite.
[0335] Example 6-6 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0336] Preparation of negative electrode sheet A first negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the first negative electrode slurry. A second negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the second negative electrode slurry. The first and second negative electrode slurries were simultaneously coated onto both surfaces of the copper foil of the negative electrode current collector at a coating weight ratio (excluding solvent) of 1:1. After drying, cold pressing, and slitting, the negative electrode sheets were obtained. The second negative electrode slurry was placed closer to the negative electrode current collector, and the first negative electrode slurry was placed further away. After drying, the first slurry formed the first negative electrode film layer, and after drying, the second slurry formed the second negative electrode film layer.
[0337] The first negative electrode active material includes pre-magnesium silicon oxide and artificial graphite, with silicon accounting for 40% of the mass of the pre-magnesium silicon oxide.
[0338] The second negative electrode active material includes artificial graphite.
[0339] Examples 6-7 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0340] Preparation of negative electrode sheet A first negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the first negative electrode slurry. A second negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the second negative electrode slurry. The first and second negative electrode slurries were simultaneously coated onto both surfaces of the copper foil of the negative electrode current collector at a coating weight ratio (excluding solvent) of 1:1. After drying, cold pressing, and slitting, the negative electrode sheets were obtained. The second negative electrode slurry was placed closer to the negative electrode current collector, and the first negative electrode slurry was placed further away. After drying, the first slurry formed the first negative electrode film layer, and after drying, the second slurry formed the second negative electrode film layer.
[0341] The first negative electrode active material includes pre-magnesium silicon oxide and artificial graphite, with silicon accounting for 50% of the mass of the pre-magnesium silicon oxide.
[0342] The second negative electrode active material includes artificial graphite.
[0343] Examples 6-8 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0344] Preparation of negative electrode sheet A first negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the first negative electrode slurry. A second negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the second negative electrode slurry. The first and second negative electrode slurries were simultaneously coated onto both surfaces of the copper foil of the negative electrode current collector at a coating weight ratio (excluding solvent) of 1:1. After drying, cold pressing, and slitting, the negative electrode sheets were obtained. The second negative electrode slurry was placed closer to the negative electrode current collector, and the first negative electrode slurry was placed further away. After drying, the first slurry formed the first negative electrode film layer, and after drying, the second slurry formed the second negative electrode film layer.
[0345] The first negative electrode active material includes pre-magnesium silicon oxide and artificial graphite, with silicon accounting for 60% of the mass of the pre-magnesium silicon oxide.
[0346] The second negative electrode active material includes artificial graphite.
[0347] Examples 6-9 Except for the following differences, the preparation of the cylindrical battery cells is the same as in Example 1.
[0348] Preparation of negative electrode sheet A first negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the first negative electrode slurry. A second negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, and conductive carbon black were mixed evenly in a mass ratio of 94:2:2:2, and then added to deionized water as a solvent. The mixture was stirred thoroughly to prepare the second negative electrode slurry. The first and second negative electrode slurries were simultaneously coated onto both surfaces of the copper foil of the negative electrode current collector at a coating weight ratio (excluding solvent) of 1:1. After drying, cold pressing, and slitting, the negative electrode sheets were obtained. The second negative electrode slurry was placed closer to the negative electrode current collector, and the first negative electrode slurry was placed further away. After drying, the first slurry formed the first negative electrode film layer, and after drying, the second slurry formed the second negative electrode film layer.
[0349] The first negative electrode active material includes pre-magnesium silicon oxide and artificial graphite, with silicon accounting for 70% of the mass of the pre-magnesium silicon oxide.
[0350] The second negative electrode active material includes artificial graphite.
[0351] Table 7
[0352] As shown in Table 7, this disclosure improves the energy density and cycle life of cylindrical battery cells by setting a first film layer away from the negative electrode current collector and a second film layer close to the negative electrode current collector. The first film layer includes silicon-based materials and carbon-based materials, and the second film layer includes carbon-based materials. The silicon-based materials also include alkali metal elements and / or alkaline earth metal elements, and the mass ratio of silicon elements in the silicon-based materials is 2% to 70%.
[0353] The above description is merely a specific embodiment of this disclosure. Those skilled in the art will clearly understand that, for the sake of convenience and brevity, the specific working processes of the systems, modules, and units described above can be referred to the corresponding processes in the foregoing method embodiments, and will not be repeated here. It should be understood that the protection scope of this disclosure is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in this disclosure, and these modifications or substitutions should all be covered within the protection scope of this disclosure.
Claims
1. A cylindrical battery cell, wherein, include: The outer casing is made of metal. The electrode assembly and electrolyte are housed within the housing; The housing includes a shell and an end cap. The shell includes a side wall and an end wall connected to the side wall. The shell has an opening. The end cap is connected to the side wall and covers the opening. The end cap and the end wall are opposite each other along the axial direction of the cylindrical battery cell. The surface of the end cap has an explosion-proof valve. The explosion-proof valve occupies 10% to 40% of the surface area of the end cap. The electrode assembly includes a negative electrode and a positive electrode. The positive electrode includes a positive current collector and a positive electrode film. The positive electrode film is disposed on at least one side of the positive current collector. The positive electrode film includes a positive active material, which includes a nickel-lithium transition metal oxide. The nickel-lithium transition metal oxide includes a modifying element M, which includes one or more of B, Y, Nb, Sn, Zr, Ti, W, Ca, Sr, S, F, Na, K, V, Ta, and Mg. The mass percentage of the modifying element M in the positive electrode film is 0.01% to 0.4%. Based on the total mass of the transition metals in the nickel-lithium transition metal oxide, the mass percentage of Ni is greater than or equal to 50%. The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer. The negative electrode film layer is provided on at least one side of the negative electrode current collector. The negative electrode film layer includes a negative electrode active material, which includes one or more of silicon-based materials and carbon-based materials. The negative electrode film layer includes a first film layer away from the negative electrode current collector and a second film layer close to the negative electrode current collector. The first film layer includes the silicon-based material and the carbon-based material, and the second film layer includes the carbon-based material. The silicon-based material further includes alkali metal elements and / or alkaline earth metal elements, and the mass percentage of silicon element in the silicon-based material is 2% to 70%.
2. The cylindrical battery cell according to claim 1, wherein, The explosion-proof valve occupies 10% to 30% of the area of the end cap surface; and / or, The modified element M has a mass percentage of 0.1% to 0.4% in the positive electrode film; and / or, Based on the total mass of the transition metals in the nickel-lithium transition metal oxide, the mass percentage of Ni is 80% to 97%.
3. The cylindrical battery cell according to claim 1 or 2, wherein, The explosion-proof valve occupies 20% to 30% of the area of the end cap surface, the modified element M occupies 0.25% to 0.4% of the mass of the positive electrode film layer, and the Ni element occupies 85% to 92% of the mass based on the total mass of the transition metal in the nickel-lithium transition metal oxide.
4. The cylindrical battery cell according to claim 1, wherein, When the modifying element M is one or more of B, Y, Nb, Sn, Zr, Ti, W, Sr, V, and Ta, the mass percentage of the modifying element M in the positive electrode film layer is 0.03% to 0.2%; and / or, When the modifying element M is one or more of S and F, the mass percentage of the modifying element M in the positive electrode film layer is 0.02% to 0.1%; and / or, When the modifying element M is one or more of Mg, Na, K and Ca, the mass percentage of the modifying element M in the positive electrode film layer is 0.05% to 0.2%.
5. The cylindrical battery cell according to claim 1, wherein, The nickel-lithium transition metal oxide particles include an inner region and an outer region. The outer region refers to the area from the outer surface of the particle to a depth of 500 nm in the direction toward the geometric center of the particle. The outer region surrounds the outer periphery of the inner region. Both the inner region and the outer region are provided with the modified element M.
6. The cylindrical battery cell according to claim 1, wherein, The positive electrode active material includes a nickel-lithium transition metal oxide matrix and a coating layer disposed on at least a portion of the surface of the nickel-lithium transition metal oxide matrix. The coating layer includes one or more of cobalt oxide and aluminum oxide, and the Dv50 of the positive electrode active material is 1 μm to 5 μm.
7. The cylindrical battery cell according to claim 1, wherein, The Dv50 of the positive electrode active material is 1.5 μm to 4 μm.
8. The cylindrical battery cell according to claim 1, wherein, The positive electrode active material includes single crystal particles and polycrystalline particles, and the polycrystalline particles account for 50% to 90% of the area of the positive electrode film.
9. The cylindrical battery cell according to claim 1, wherein, The molar percentage of Ni in the transition metal elements of the nickel-lithium transition metal oxide is above 85%; and / or, The reversible specific capacity of the nickel-lithium transition metal oxide is from 200 mAh / g to 225 mAh / g.
10. The cylindrical battery cell according to claim 1, wherein, The nickel-lithium transition metal oxide also includes the general formula Li a Ni b A c O e The nickel-lithium transition metal oxide matrix, wherein 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 1≤e≤2, and A includes one or more of Mn, Al and Co.
11. The cylindrical battery cell according to claim 1, wherein, The carbon-based material includes one or more of artificial graphite, natural graphite, hard carbon, and soft carbon; and / or, The silicon-based materials include one or more of silicon-carbon materials, elemental silicon, silicon oxides, silicon-nitrogen composites, and silicon alloys.
12. The cylindrical battery cell according to claim 1, wherein, The mass percentage of Si element in the negative electrode film is 3% to 20%; and / or, The silicon-based material includes a silicon-carbon material, which includes a porous carbon substrate and silicon located in the pores of the porous carbon substrate.
13. The cylindrical battery cell according to claim 1, wherein, The silicon-based material contains 2% to 20% silicon by mass.
14. The cylindrical battery cell according to claim 1, wherein, The electrolyte includes functional additives, which include one or more of sulfur-containing additives, boron-containing additives, fluorine-containing additives, and carbonate additives. The functional additives account for 0.05% to 7% of the mass of the electrolyte.
15. The cylindrical battery cell according to claim 14, wherein, The sulfur-containing additive includes one or more of 1,3-propenesulfonate lactone, vinyl sulfate, and vinyl sulfite; and / or, The boron-containing additive includes one or more of lithium difluorophosphate and lithium bis(oxalato)borate; and / or, The fluorinated additive includes one or more of fluoroethylene carbonate, lithium difluorooxalate borate, and lithium difluorophosphate; and / or, The carbonate additives include one or more of dimethyl carbonate, ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate.
16. The cylindrical battery cell according to claim 1, wherein, The electrolyte also includes an electrolyte salt, which includes one or more of lithium hexafluorophosphate, lithium difluorophosphate, and lithium bis(oxalato)borate.
17. The cylindrical battery cell according to claim 16, wherein, The molar concentration of the electrolyte salt is from 0.7 mol / L to 1.5 mol / L.
18. The cylindrical battery cell according to claim 1, wherein, The electrode assembly further includes a separator membrane located between the positive electrode and the negative electrode. The separator membrane includes a base film and a coating located on at least one side of the base film. The coating includes a first coating away from the base film and a second coating close to the base film. The first coating includes ceramic particles, and the second coating includes polymer particles.
19. The cylindrical battery cell according to claim 18, wherein, The base material of the sidewall is steel, and the thickness of the sidewall is 0.2 mm to 0.6 mm.
20. The cylindrical battery cell according to claim 1, wherein, The dimension of the outer casing along the axial direction of the cylindrical battery cell is 1.3 to 2.6 times the outer diameter of the outer casing.
21. The cylindrical battery cell according to claim 1, wherein, The outer casing has a dimension of 50 mm to 150 mm along the axial direction of the cylindrical battery cell; and / or, The outer diameter of the outer casing is 30mm to 80mm.
22. The cylindrical battery cell according to claim 1, wherein, The outer diameter of the outer shell is 40mm to 60mm.
23. A battery device, wherein, It includes the cylindrical battery cell as described in any one of claims 1-22.
24. An electrical appliance, wherein, Includes the cylindrical battery cell according to any one of claims 1-22.
25. An electrical appliance, wherein, Includes the battery device as described in claim 23.
Citation Information
Patent Citations
Modified high-nickel ternary positive electrode material as well as preparation method and application thereof
CN117981115A
Battery monomer, battery and electric device
CN118198514A